2022
DOI: 10.3390/dj10080142
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Dissemination of Aerosol and Splatter Using Suction Device during Ultrasonic Scaling: A Pilot Study

Abstract: Objective: This study compared the aerosol and splatter diameter and count numbers produced by a dental mouth prop with a suction holder device and a saliva ejector during ultrasonic scaling in a clinical setting. Methodology: Fluorescein dye was placed in the dental equipment irrigation reservoirs with a mannequin, and an ultrasonic scaler was employed. The procedures were performed three times per device. The upper and bottom board papers were placed on the laboratory platform. All processes used an ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Virus can also potentially have a wider transmission range compared to bacteria due to its smaller size [ 10 ]. Zemouri et al revealed that the bacteria-containing aerosols generated by dental treatments were mainly distributed around patient’s head, which align with our results on aerosol distribution [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Virus can also potentially have a wider transmission range compared to bacteria due to its smaller size [ 10 ]. Zemouri et al revealed that the bacteria-containing aerosols generated by dental treatments were mainly distributed around patient’s head, which align with our results on aerosol distribution [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, instrumental methods can measure particle concentration but are limited to particles of a fixed size, making it challenging to discern viral particles [ 22 , 23 ]. Similarly, filter paper, optical, and spectroscopic methods are unable to measure particle concentration, providing only droplet counts [ 9 , 20 , 24 , 25 ]. Microbiological methods typically prioritize the detection of alpha-hemolytic streptococci or anaerobes, often neglecting viruses [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study of female dentists, it was mentioned that they provide more scaling and restorative services than males although the differences might not be statistically significant [97] as in our study. This could also explain our findings, because after scaling it is known that the unit brings high levels of contaminant material into the system through blood suction during the process [49], thus forcing dentists to perform a stricter disinfection protocol. As reported in the study of Reza et al [97], female dentists administered more pediatric treatments than their male colleagues, though this was not statistically significant.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, sufficient guidelines about how to decontaminate handpieces are available [19], but most of the dentists in our study and elsewhere [105,106] are unaware of these guidelines, forgetting, for example, that overnight bacterial accumulation in the handpieces can be significantly reduced by allowing water-cooled handpieces to run and to discharge water into a sink or container for several minutes at the beginning of the clinic day [101]. In the study of Schalli et al [101], though, the fact that 92.9% of water samples taken after procedures during which no spray water was used showed an increase in protein concentration illustrates that the contamination cannot be due solely to the retraction of spray water and that differences in the maintenance and antiseptic protocols used in different offices and the rotational speed of the handpiece could explain a certain dilution [44,49,103]. Other techniques such as preprocedural mouth rinsing with chlorhexidine [107], essential oil, povidone-iodine or water before ultrasonic scaling could reduce bacterial contamination on aerosol formation and cross-contamination [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation